Procedural Deficiencies in Administrative Tribunals of Bangladesh: Exploring Alternative Tactics - Aktar, Sharmin (Dhaka University Law Journal, 2024)
The present article demonstrates that a troublesome reality is now being faced by Administrative Tribunals, leaving a room highlighting problems that have been unaddressed since its inception. It is found that the jurisprudential concept of locus standi, so far as Administrative Tribunals are concerned, is not wide and comprehensive, even then it need not be extended due to its short domain of jurisdiction as to subject matter. Furthermore, there is no scope to condone the delay according to relevant provisions. In addition, the Act of 1980 does not mysteriously fix a period for the restoration of a case or setting aside an ex parte order. Whereas most of the litigations in Tribunals concern a lack of procedural fairness in departmental proceedings, therein the principle of ‘Natural Justice’ is not recognized. These lapses seriously endangered the future of this justice system but neither the legislature nor the judiciary has so far taken any serious step to check these realities. Therefore, scattered procedural complexities have been accommodated in this article based on the Act of 1980 as well as the Rules of 1982; and cases and interviewing have been used as the point of reference, but at the same time earnest effort has been spent for finding out solutions, guided by expediency and tradition. Dhaka University Law Journal, 2023, 34 (2), 67-95